Applied Mathematics 2019
DOI: 10.5772/intechopen.82832
|View full text |Cite
|
Sign up to set email alerts
|

What Determines EP Curve Shape?

Abstract: Propose use kurtosis divided by skewness squared as shape factor, and use the global or conditional minimum/maximum of this shape factor for selecting and differentiating distribution families. Semi-empirical formulas for that lower/upper bound are calculated for various distribution families, with the aid of Computer Algebra System, for fitting hard to match distributions. Previous studies show high CV distribution is hard to fit and simulate, this study extends that conclusion to cases with low CV but still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…In signal processing, there is another definition of shape factor as the root mean square divided by the mean of the absolute value, https://www.mathworks.com/help/predmaint/ug/signal-features.html. This is a variant of CV, or the square root of the SF4[2] in Wang (2019a). We studied CV in Wang (2018a) and further research lead to our higher order shape factor definition that are more intrinsic to the shape of the distribution PDF, Wang (2018b and2019a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In signal processing, there is another definition of shape factor as the root mean square divided by the mean of the absolute value, https://www.mathworks.com/help/predmaint/ug/signal-features.html. This is a variant of CV, or the square root of the SF4[2] in Wang (2019a). We studied CV in Wang (2018a) and further research lead to our higher order shape factor definition that are more intrinsic to the shape of the distribution PDF, Wang (2018b and2019a).…”
Section: Discussionmentioning
confidence: 99%
“…This is a variant of CV, or the square root of the SF4[2] in Wang (2019a). We studied CV in Wang (2018a) and further research lead to our higher order shape factor definition that are more intrinsic to the shape of the distribution PDF, Wang (2018b and2019a). The CV, Gini index, and normalized skewness, defined as the sign-keeping square root of the reciprocal of the shape factor, are indeed related to each other from our empirical study, which showed that CV is almost identical to Gini index, and are the base part or lower envelope of the normalized skewness; these are topics for a different research thesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations